Sentence-final expressions-- rasii and yoo : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Japanese at Massey University - Tochigi, Asuka (Massey University, 2003)
In the Japanese language there is a group of sentence-final expressions, which indicate the speaker's attitude toward the proposition they are maintaining. Included in this group are expressions such as kamosirenai, tigainai, hazu, yoo, mitai, rasii, soo (hearsay) and (si) soo. This thesis is an examination of the functions of the two expressions yoo and rasii. In many cases rasii and yoo are interchangeable in the respect that they work as evidential markers that the speaker makes a judgment based on evidence. However there is a subtle difference between them. The distinction between them is made by the degree of the speaker's perception. Even though the same types of evidence may be used, rasii indicates that a lesser degree of the speaker's perception is involved, whereas yoo indicates that a higher degree of the speaker's perception is involved. A closer investigation of the uses of rasii and yoo, based on Brown and Levinson's politeness theory, is carried out and it is concluded that both rasii and yoo work as politeness strategies. That is, the speaker utilises the function of either rasii or yoo to satisfy the other's feeling and to establish a good rapport between the speaker and the addressee in human interactions, as well as to maintain the speaker's own desire.
Keywords: Japanese language; Grammar